2007
DOI: 10.1093/ecam/nem106
|View full text |Cite
|
Sign up to set email alerts
|

Ear Acupuncture in European Traditional Medicine

Abstract: Auricular acupuncture is a diagnostic and treatment system based on normalizing the body's dysfunction through stimulation of definite points on the ear. Rudimentary forms of acupuncture which probably arose during the Stone Age have survived in many parts of the world right down to present day. It was used in the ancient Egypt, Rome, Greece and all the Mediterranean area. It is a microacupuncture technique similar to reflexology, and was first described in France in 1950 by Paul Nogier who is considered the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 18 publications
1
101
0
19
Order By: Relevance
“…The stimulation of the reflex point in the ear provides an action of relief in symptoms in distant parts of the body (20) . Stimulating points may also activate small myelinated nervous fibers that send impulses to the spine, brain, pituitary and hypothalamus, causing the release of endorphins in the blood in the treatment of pain (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of the reflex point in the ear provides an action of relief in symptoms in distant parts of the body (20) . Stimulating points may also activate small myelinated nervous fibers that send impulses to the spine, brain, pituitary and hypothalamus, causing the release of endorphins in the blood in the treatment of pain (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, auricular acupuncture employs semipermanent or systemic needles as instruments to stimulate the points (9) . Seeds or magnets can also be utilized to perform the stimulation (10) .…”
Section: Chinese Auriculotherapy Is a Traditional Chinesementioning
confidence: 99%
“…When the reflex points in the ear are stimulated the relief of symptoms in distant parts of the body can be achieved (9) . Stimulating points can also activate small myelinated nerve fibers that send impulses to the spinal column, brain, pituitary and hypothalamus, causing the release of endorphins into the blood in the treatment of pain (11) .…”
Section: Chinese Auriculotherapy Is a Traditional Chinesementioning
confidence: 99%
“…The Egyptologist Alexandre Varille has demonstrated that women in ancient Egypt, who did not want any more children, had their external ear pricked with a needle or cauterized with heat [1]. Mediterranean sailors' wearing gold earrings were not just used as decorations, but were said to improve vision [2]. Hippocrates, who was the father of Greek medicine, reported doctors made small openings in the veins situated behind the ear to facilitate ejaculation and reduce impotency problems [3].…”
Section: Ancient Applications Of Auricular Treatmentsmentioning
confidence: 99%
“…Cutting of veins situated behind the ear was used to treat leg pain as well [4]. The Greek physician Galen introduced Hippocratic medicine to the Roman Empire in the second century CE, commentating on the healing value of scarification at the outer ear [2]. After the fall of Roman Empire, the medical records of Egyptian, Greek and Roman medicine were best preserved in ancient Persia and Arabian world.…”
Section: Ancient Applications Of Auricular Treatmentsmentioning
confidence: 99%